Acute Bacterial Prostatitis – a review of current literature - Zając, Piotr; Węgrzyn, Jan; Fijałkowski, Łukasz; Nosal, Aleksandra; Czarnecki, Adam; Galanty-Ochyra, Aleksandra; Serwońska , Karolina; Pastuszka , Artur; Jabłońska, Olga; Klimas, Filip (Journal of Education, Health and Sport, 2025)
Introduction and purpose Acute bacterial prostatitis (ABP) is a troublesome prostate infection that manifests with a range of irritative urinary symptoms, pelvic discomfort, potentially progressing to urinary retention. ABP can cause severe complications, including prostatic abscess and sepsis. Hence the need to collect and share current knowledge on risk factors, diagnosis and treatment. A brief description of the state of knowledge ABP is in most cases caused by E. Coli. Symptoms are non-specific and many patients lack identifiable risk factors. It is important to perform cautious digital rectal examination, urine analysis and culture when diagnosing acute bacterial prostatitis. Oral fluoroqinolones are the first-line outpatient treatment for non-complicated cases. Patients presenting symptoms indicative of urosepsis should be hospitalized and treated with intravenous antibiotics. Increasing antimicrobial resistance observed among Enterobacterales necessitates the search for new therapeutic agents. Lack of clinical improvement after initial treatment may indicate resistant pathogens or the development of prostatic abscess (PA). PA can be diagnosed with transrectal ultrasound and may require surgical intervention. Without proper treatment ABP can transform to chronic bacterial prostatitis. Transrectal prostate biopsy is associated with higher risk of ABP therefore antibiotical prophylaxis should be used. Conclusions ABP is not the most common type of prostatitis, but it should not be overlooked. Better knowledge about risks associated with ABP and available treatment leads to more accurate therapy choices. Awareness of the challenges posed by antibiotic resistance leads to the development of new, more effective treatments.